Canadian Club Cafe in the Hiram Walker Exhibit (Hiriam Walker & Sons)
6 Daily Shows - Nationally Known Orchestras, Style Shows, Opera Stars - Special features daily by World's Famous Entertainers - From Noon till 2 A.M. See the complete modern bottling line in operation.